Developmental surface and phonological dysgraphia in German 3rd graders - Cholewa, Jürgen; Mantey, Stefanie; Heber, Stefanie; Hollweg, Wibke (Reading and writing, 2010)
The investigation of developmental reading and spelling disorders within the framework provided by cognitive neuropsychology has yielded interesting results for several alphabetic orthographies, for example English, Italian, and French. However, this approach has not attracted much attention in German speaking countries up to now. The following study, carried out with 35 German dysgraphic 3rd graders provides evidence that there is no less reason to apply this line of research to German children than to children acquiring other alphabetic orthographies. By evaluating the individual scores of the dysgraphic children on spelling nonwords and orthographically irregular or inconsistent words against the corresponding mean scores established for two non-dysgraphic control samples (grade-matched and 2nd grade), nine children could be assigned to the surface dysgraphic and 12 to the phonological dysgraphic subtype. In order to restrict the range of cognitive deficits which might have caused the spelling patterns of the two dysgraphic subgroups at more distal links of the causal chain, individual performance profiles were determined for several spelling-related phonological and visual-graphemic tasks. On average, the phonological dysgraphic children showed poorer performance in different phonological tasks than the children assigned to the surface subtype. In addition, both subgroups showed subnormal skills in visual-graphemic tasks. Dissociations between the different spelling related tasks were observed not only between but also within the subgroups. This may reflect individually varying cognitive processing deficits underlying developmental dysgraphia in German.
Published online: 18 December 2008
Gesehen am 13.03.2023